2011
DOI: 10.1158/1541-7786.mcr-11-0080
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Dependent Cleavage of the Laminin Receptor α6β1 in Prostate Cancer

Abstract: The laminin binding integrin α6β1 plays a major role in determining the aggressive phenotype of tumor cells during metastasis. Our previous work has shown that cleavage of the α6β1 integrin to produce the structural variant α6pβ1 on tumor cell surfaces is mediated by the serine protease uPA. Cleavage of α6β1 increases tumor cell motility, invasion, and prostate cancer metastasis, and blockage of uPA inhibits α6pβ1 production. In human tumors uPA and uPAR are expressed in tumor cells and tumor associated macrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…CTCs produce proinflammatory cytokines and chemokines that draw tumor associated macrophages (TAMs) to the tumor-cell clusters from circulation [32]. Macrophages are known to aid prostate cancer tumor-cell invasion and migration through modification of the adhesion function of laminin-binding integrins that interact with laminin 511 [32], suggesting that tumor clusters themselves contain a specialized pro-metastatic microenvironment. Increased retrieval of the CTCs, including the CTC-clusters and associated cells, will likely aid in treatment stratification of prostate cancer (reviewed in [5]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTCs produce proinflammatory cytokines and chemokines that draw tumor associated macrophages (TAMs) to the tumor-cell clusters from circulation [32]. Macrophages are known to aid prostate cancer tumor-cell invasion and migration through modification of the adhesion function of laminin-binding integrins that interact with laminin 511 [32], suggesting that tumor clusters themselves contain a specialized pro-metastatic microenvironment. Increased retrieval of the CTCs, including the CTC-clusters and associated cells, will likely aid in treatment stratification of prostate cancer (reviewed in [5]).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work shows the functional role of one LBI (α6β4) as a mediator of endothelial cell protection in the setting of excessive mechanical stretch relative to lung injury [63]. LBI expression patterns have clinical significance for several epithelial-derived malignancies, for example the α6β1 integrin receptor is conserved in prostate cancer [39], is expressed on prostate tumor cells undergoing PNI [13], and acts as a marker in the aggressive phenotype of tumor cells during cancer progression [14,32,60,64]. The LBIs are especially associated with the invasion and metastasis of human prostate cancer, traversing through muscle [39,6569].…”
Section: Resultsmentioning
confidence: 99%
“…Cleavage of the α6β1 integrin by uPA has been shown in in vivo studies to increase tumor cell motility, invasion, and prostate cancer metastasis (Ports et al 2009). Further in vitro studies indicated that this process may be mediated by TAMs (Sroka et al 2011). Likewise, the cathepsin proteases, and specifically cathepsin K and cathepsin S, are also of interest in this regard.…”
Section: Macrophages In Prostate Cancermentioning
confidence: 99%
“…Recently, published work indicates that ITGA6 cleavage is closely associated with uPAR and uPA levels [12]. These observations of increased ITGA6 cleavage prompted us to determine if uPAR levels were increasing as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the necessary role of uPA in cleaving ITGA6, recent work by our group has shown that macrophages can stimulate uPA/uPAR production in tumor cells and increase ITGA6 cleavage. These data suggested that tumor activated macrophages promote prometastatic integrin-dependent pericellular proteolysis and the metastatic phenotype [12]. Furthermore, ITGA6 cleavage has been shown to contribute to cell invasion and migration on laminin, and inhibition of ITGA6 cleavage was shown to substantially delay the onset of bone metastasis and promote curative-type bone metastasis lesions in xenograft mouse models [1315].…”
Section: Introductionmentioning
confidence: 99%